Quranic Mental Health amidst pandemic: a cultural-hermeneutic reading to the Salawat community in Indonesia. - Putra, D. I. Ansusa; Farida, Umma; Sartika, Dani; Kasdi, Abdurrohman; Handayani, Silvia (Mental Health, Religion & Culture, 2023)
The COVID-19 pandemic has created excessive anxiety and psychological disaster globally. People try to calm their souls by performing religious rituals such as Salawat. This research explains the uniqueness of Quran and hadith-based mental health in dealing with pandemics using the Salawat tradition in Indonesia. This is qualitative research with data collected from the Salawat communities through in-depth interviews and observations, then analyzed using Cognitive Behavior Therapy (CBT) to determine the level of mental health and its relationship with the Quranic Mental Health concept. David Tracy's cultural-hermeneutic theory was used to understand how the Salawat community reaches good mental health in dealing with pandemics. It discusses the Quranic Mental Health from the perspective of hermeneutic and culture, examines links with psychological concepts such as religious phenomenon, and describes preliminary empirical evidence related to the mental construct. It has potentially valuable implications for researchers and clinicians interested in Islamic psychology.